COST CLASSIFICATION AND ORGANIZATIONAL ASPECTS OF MANAGEMENT ACCOUNTING PROCESSES IN ANIMAL HUSBANDRY (Scientific Journal of Actuarial Finance and Accounting, 2024)
The article discusses the organizational aspects of the processes of cost classification and management accounting in livestock farming. A classification of production costs in livestock farming is proposed. Conclusions have been drawn on improving the organizational aspects of management accounting processes in livestock farming.